2017
DOI: 10.1152/jn.00322.2017
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of molecularly defined spinal interneurons engaged in mammalian locomotor pattern generation

Abstract: Mapping the expression of transcription factors in the mouse spinal cord has identified ten progenitor domains, four of which are cardinal classes of molecularly defined, ventrally located interneurons that are integrated in the locomotor circuitry. This review focuses on the properties of these interneuronal populations and their contribution to hindlimb locomotor central pattern generation. Interneuronal populations are categorized based on their excitatory or inhibitory functions and their axonal projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 226 publications
0
45
0
Order By: Relevance
“…In normal rats, as in primates, S1 CST terminals synapse in the (contralateral) dorsal horn primarily on to the presumed axons/dendrites of intraspinal neuronal populations (Côté, Murray, & Knikou, ; Gosgnach et al, ; Schieber, ; Ziskind‐Conhaim & Hochman, ). Target neurons may include local reflex, long and short range propriospinal (Filli & Schwab, ) and commissural interneuronal populations (Bannatyne, Edgley, Hammar, Jankowska, & Maxwell, ; Jankowska et al, ; Soteropoulos, Edgley, & Baker, ), which in turn connect with motor neurons, and/or regulate (or gate) ascending tracts (i.e., the dorsal columns, spinocerebellar and spinothalamic pathways).…”
Section: Discussionmentioning
confidence: 99%
“…In normal rats, as in primates, S1 CST terminals synapse in the (contralateral) dorsal horn primarily on to the presumed axons/dendrites of intraspinal neuronal populations (Côté, Murray, & Knikou, ; Gosgnach et al, ; Schieber, ; Ziskind‐Conhaim & Hochman, ). Target neurons may include local reflex, long and short range propriospinal (Filli & Schwab, ) and commissural interneuronal populations (Bannatyne, Edgley, Hammar, Jankowska, & Maxwell, ; Jankowska et al, ; Soteropoulos, Edgley, & Baker, ), which in turn connect with motor neurons, and/or regulate (or gate) ascending tracts (i.e., the dorsal columns, spinocerebellar and spinothalamic pathways).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic approaches to label specific developmental classes of spinal neurons have allowed investigators to begin dissecting the complex circuitry of the spinal cord (Grillner and El Manira, 2015;Lu et al, 2015;Kiehn, 2016;Gosgnach et al, 2017;Ziskind-Conhaim and Hochman, 2017;Dougherty and Ha, 2019). Developmental studies have identified 10 progenitor domains that give rise to six dorsal (dI1-6) and four ventral (V0-V3) classes of propriospinal neurons.…”
Section: Developmental Neuron Classes Perform Distinct Functionsmentioning
confidence: 99%
“…In normal rats, as in primates, S1 CST terminals synapse in the (contralateral) dorsal horn primarily on to the presumed axons/dendrites of intraspinal neuronal populations (Schieber, 2007;Gosgnach et al, 2017;Ziskind-Conhaim & Hochman, 2017;Côté et al, 2018). Target neurons may include local reflex, long and short range propriospinal (Filli & Schwab, 2015) and commissural interneuronal populations (Bannatyne et al, 2003;Jankowska et al, 2009;Soteropoulos et al, 2013), which in turn connect with motor neurons, and/or regulate (or gate) ascending tracts (i.e.…”
Section: Dorsal Horn Circuitry and The Role Of S1 Cst Terminal Sproutmentioning
confidence: 99%